Ecobehavioral Analysis of the Experiences of Students With Complex Support Needs in Different Classroom Types. (December 2022) - Zagona, Alison L.; Kurth, Jennifer A.; Lockman Turner, Elissa; Pace, Jesse; Shogren, Karrie; Lansey, Kirsten; Jameson, Matt; Burnette, Kristin; Mansouri, Mary; Hicks, Tyler; Gerasimova, Daria
Students with complex support needs frequently experience restrictive educational placements such as self-contained and separate school classrooms. Given the need to support students with complex support needs to experience positive outcomes and make progress in the general education curriculum, there is a need to investigate the characteristics of the classroom contexts in which they are learning. The purpose of this study was to use ecobehavioral assessment observation methods to investigate how student behaviors, educator behaviors, and classroom ecology vary across general education, resource, self-contained, and separate school classrooms. We observed 116 students with complex support needs across the United States, and results indicated that contextual features of resource, self-contained, and separate school classrooms do not offer superior levels of instruction or supports for students with complex support needs as compared with general education classrooms. We were more likely to observe no one interacting with the focus student, no instruction, and the presence of distractions in self-contained and separate school classrooms compared with general education classrooms. Implications for policy, research, and practice are presented.